Pengaturan Waktu Pemberian Makanan Tambahan dengan Status Gizi Berdasarkan Tinggi Badan Balita - Syaiful Bachri (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2020)
In Bondowoso, the prevalence of stunting in February 2019 reached 17.54% of 45,002 toddlers. Stunting is closely related to inadequate nutritional intake, one of which is timing of suplementary feeding. The purpose of research was to determine the relationship of timing of suplementary feeding with nutritional status based on toddler’s height. This research was a correlational study with a case control approach. Population are 46 and 41 toddlers sample’s with proportional random sampling technique. The instrument used questionnaires, microtoise and z score’s aplication. The results showed that the value of toddlers with a history of correct time of giving suplementary feeding 56.1%, while 43.9% with a history of giving suplementary feeding are not appropriate. Toddlers who have normal height are 56,1%, who experienced stunting a number of 43.9%. From the results of the Spearman rank correlation test obtained a p value 0.310 <α (0.05) which means that H0 is rejected or means that there is a significant relationship between the timing of suplementary feeding and nutritional status based on height of toddlers. Expected interesting education is needed for the community about time of give suplementary feeding on time to prevent stunting in toddlers.